The primal blueprint - Sisson, Mark, 1953- (Primal Blueprint Publishing, 2019)
The New Primal Blueprint serves as the ultimate road map for anyone wishing to make the shift from flawed conventional wisdom about diet and exercise to a healthy, happy empowering lifestyle patterned after the evolutionary-tested behaviors of our hunter-gatherer ancestors. The book details the ten immutable Primal Blueprint lifestyle laws that enable empower you to reprogram your genes to direct in the direction of weight loss, health, and longevity. The Primal Blueprint laws are validated by two million years of human evolution as well as an ever-expanding body of contemporary scientific research. Sisson<U+2019>s philosophy was originally met with skepticism as he aggressively challenged numerous mainstream health tenets. Eight years later, mainstream medical and health science are validating the Primal Blueprint tenets assertions that a high-carb, grain-based diet will make you fat, tired, and sick; that a consistent routine of medium-to-difficult cardiovascular workouts can actually compromise your health and longevity and increase risk of heart disease; and that consuming (whole food sources of) fat and cholesterol does not lead to heart disease as we have been led to believe, but rather offers many health benefits.